Kemampuan Isolat Bakteri Selulolitik Asal Tanah Gambut Sebagai Pendegradasi Limbah Kulit Buah Jagung (Zea mays. L) - Riza Linda, Erin Nurlia, Siti Khotimah, (Universitas Tanjungpura, 2015)
The aim of this research was to cognize capability of cellulolytic bacteria isolated from peat soil in degradation cornhusk waste. The research was conducted from March to April 2014. The celluloytic bacteria used in this research were Acetobacter (Ab), Acidomonas (Ad), and Cellvibrio (Cv). This research utilized Completely Randomized Design (CRD) consist of 5 treatments, which were treatment A (control), B 2g of cornhusk with 10% bacterial liquid culture (2.6ml Cv and 2.6ml Ad) added, C 2g of cornhusk with 10% bacterial liquid culture (2.6ml Ad and 2.6ml Ab) added, D 2g of cornhusk with 10% bacterial liquid culture (2.6ml Cv and 2.6ml Ab) added, and E 2g of cornhusk with 10% bacterial liquid culture (1.8ml Cv, 1.8ml Ab, and 1.8ml Ad) added. The combination of Cellvibrio, Acidomonas, and Acetobacter bacteria on each treatment were capable of decomposing the cornhusk waste with decrease in the substrateweight about 19,3-21,63%, with 2.452-2,965% protein contents, 1.254-1.864% fat contents, and 3.176-4.543% carbohydrate contents. The combination of Cellvibrio and Acetobacter bacteria were faster than the other combinations in decomposing the corn husk waste measured by substrate decomposition rate valuewhich was 3.090% in 7 days.